Routledge handbook of Islam in Southeast Asia - Aljunied, Syed Muhd. Khairudin, 1976- (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This handbook explores the ways in which Islam, as one of the fastest growing religions, has become a global faith for both Muslims and non-Muslims in Southeast Asia with its universality, inclusivity and shared features with other Islamic expressions and manifestations. It offers an up-to-date, wide-ranging, comprehensive, concise, and readable introduction to the field of Islam in Southeast Asia. With specific themes of pertinent contemporary relevance, the contributions by experts in the field provide fresh insights into the roles of states, societies, scholars, social movements, political parties, social movements, economic institutions, sacred sites, and other forces that structured the faith over many centuries. The handbook is structured in three parts: Muslim Global Circulations - Marginal Narratives - Refashioning Pieties. This handbook stands out as a single and synergistic reference work that explores the ebb and flow of Islam seeking to decenter many existing assumptions about it in Southeast Asia. It will be an indispensable resource for scholars, students, and policymakers working on Islam, Muslims, and their interactions with other communities in a plural setting"--
Muslim Global Circulation -- Marginal Narratives -- Refashioning Pieties.
Keywords: Islam -- Southeast Asia; Muslims -- Southeast Asia; RELIGION / Islam / General; SOCIAL SCIENCE / Ethnic Studies / General